40 - STRENGTHS AND WEAKNESSES OF FIGURE SKATING IN SLOVAKIA (Fiep Bulletin - online, 2021)
The article deals with the figure skating course of two countries that were a common state 30 years ago and operated based on one union with one management. Due to the political events in 1992, the country was divided and the centralized management of figure skating also had to disintegrate. From one union, which was run from Prague became two unions, operating independently of each other. Figure skating in Slovakia suffered from the first moment, mainly due to leaving the management of figure skating to the original association in Prague. Many sports experts and officials continued their activities for the Czech Republic. Despite the re-emerging association, the Slovak Republic strives for the best possible conditions not only for athletes but also for sports professionals. The study deals with the search for innovations and assistance to the Slovak Republic to find and eliminate shortcomings.
Keywords: figure skating; Slovak Republic; SWOT analyses